Advanced hybrid information processing : second EAI International Conference, ADHIP 2018, Yiyang, China, October 5-6, 2018, Proceedings /: second EAI International Conference, ADHIP 2018, Yiyang, China, October 5-6, 2018, Proceedings. (2019) - Unknown
No abstract available